2010
DOI: 10.1021/ja1057746
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Magnetic Bistability in Molecule-Based Magnets: A First-Principles Bottom-Up Study of the TTTA Crystal

Abstract: The magnetic bistability present in some molecule-based magnets is investigated theoretically at the microscopic level using the purely organic system TTTA (1,3,5-trithia-2,4,6-triazapentalenyl). The TTTA crystal is selected for being one of the best-studied molecule-based systems presenting magnetic bistability. The magnetic properties of the high- and low-temperature structures (HT and LT phases, respectively) are accurately characterized by performing a First-Principles Bottom-Up study of each phase. The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 45 publications
6
60
0
1
Order By: Relevance
“…However,i nh ysteretic spin-switch systems, the LT !HT transition takes place at ad ifferent temperature than that of the HT!LT transition. [23,24] Among the group of bistable DTAr adicals, the case of 1,3,5-trithia-2,4,6-triazapentalenyl (TTTA) is especially remarkable, since its bistability region spans 70 degrees and encompassesr oom temperature (T c› = 310 K, T cfl = 230 K) [7,[25][26][27][28][29][30][31][32][33][34][35] (Figure 1a). Bistable materials based on transition-metal complexes have been associated with spin transitions for many years [3][4][5] ,b ut recent work has demonstrated that purely-organic radicals can also be versatile building blocks to achievebistability.…”
Section: Introductionmentioning
confidence: 99%
“…However,i nh ysteretic spin-switch systems, the LT !HT transition takes place at ad ifferent temperature than that of the HT!LT transition. [23,24] Among the group of bistable DTAr adicals, the case of 1,3,5-trithia-2,4,6-triazapentalenyl (TTTA) is especially remarkable, since its bistability region spans 70 degrees and encompassesr oom temperature (T c› = 310 K, T cfl = 230 K) [7,[25][26][27][28][29][30][31][32][33][34][35] (Figure 1a). Bistable materials based on transition-metal complexes have been associated with spin transitions for many years [3][4][5] ,b ut recent work has demonstrated that purely-organic radicals can also be versatile building blocks to achievebistability.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] First, one selects all possible magnetically relevant pairs of radicals in the crystal by analysis of the crystal packing from the X-ray resolved experimental structure. As for the DTA-based crystals, although the spin density of a DTA radical is delocalized over the atoms of the entire DTA-ring (see the ESI † Section 1), the pairs of radicals have been chosen based on the N*Á Á ÁN* distance, where N* refers to the nitrogen atom that formally holds the unpaired electron (Fig.…”
Section: Methodological Detailsmentioning
confidence: 99%
“…16 Let us now briefly describe the main features of the compounds under study. TTTA exhibits bistability at room temperature (namely, T Ck = 220 K to T Cm = 315 K).…”
Section: Introductionmentioning
confidence: 99%
“…Computational studies by Novoa indicate that the diamagnetism associated with the LT phase can be attributed to an open-shell singlet rather than closed-shell singlet configuration. 43 The magnetism of the paramagnetic HT phase can be modelled as a one-dimensional chain (J/k = -320 K) consistent with strong antiferromagnetic interactions along the stacking direction with weaker inter-chain interactions.…”
Section: Trithiatriazinyl Ttta: a Case Studymentioning
confidence: 99%